2008
DOI: 10.1007/s10347-007-0133-1
|View full text |Cite
|
Sign up to set email alerts
|

High-energy sedimentary events in lagoonal successions of the Upper Silurian of Podolia, Ukraine

Abstract: Three Late Silurian carbonate proWles of the Malynivtsy and Skala Formations from Podolia (western Ukraine) are discussed in terms of sedimentation dynamics. Their common feature is the appearance of thick, stromatoporoid-rich beds within Wne-grained peritidal deposits. These intercalations are composed of fossils typical of oVshore sedimentary environments. In the most spectacular case, a channel, several tens of metres wide and inWlled with stromatoporoids, is incised in a peritidal cyclic complex. The succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 44 publications
3
41
0
Order By: Relevance
“…Points i-iv listed above and discussed in the following chapters of this paper summarize the results of the studies published in the authors' consecutive papers (Skompski et al 2008;Łuczyński et al 2009. Our understanding of the nature of the high-energy sedimentary events and of their impact on the facies record of the Silurian successions of Podolia evolved slightly during these years, and this is also presented here.…”
Section: Introductionmentioning
confidence: 83%
“…Points i-iv listed above and discussed in the following chapters of this paper summarize the results of the studies published in the authors' consecutive papers (Skompski et al 2008;Łuczyński et al 2009. Our understanding of the nature of the high-energy sedimentary events and of their impact on the facies record of the Silurian successions of Podolia evolved slightly during these years, and this is also presented here.…”
Section: Introductionmentioning
confidence: 83%
“…The continuing rapid increase in sea level has caused a retrogradational facies shift, cannibalistic disintegration of the previously deposited sediments and, finally, high dynamic deposition of the upper bio/lithoclastic limestone/dolomite complex. In this stage of the platform's development, the appearance of tidal channels (Konovka village (9) section; but also other Upper Silurian sections in Podolia (Skompski et al 2008)) is a most expected feature. In consequence, it appears that the extremely shallow-water parts of the platforms, identified as tidal plains, have a surprisingly large growth potential.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier studies (Skompski et al 2008;Łuczyński et al 2009, 2014 have revealed that part of these beds, particularly those in the higher part of the Silurian succession, are in fact represented by sediments composed of material redeposited shoreward and derived from open marine regions. One can assume that some of the stromatoporoid biostromes on Gotland are of a similar origin (compare, Kershaw 1990).…”
Section: Introductionmentioning
confidence: 96%
“…11). In spite of the facies model of Einasto et al (1986), where the Silurian carbonate platform of Podolia is treated as rimmed, it is assumed here that a carbonate ramp is a more appropriate model due to the very low-relief and spatial discontinuity of the biostromes and reef mounds and the epeiric character of the Podolian part of the basin (compare Eriksson and Calner 2008;Skompski et al 2008). The first recognizable element of stratal architecture is the sequence boundary (SB) marking the top of the Isakivtsy Fm.…”
Section: The Record Of Sea-level Changesmentioning
confidence: 99%